Analisis Pemahaman Konsep menggunakan Certainty of Response Index (CRI) pada Materi Gerak Lurus - Wahyu Tulus Setyantini; Dwi Teguh Rahardjo; Suharno Suharno (Jurnal Materi dan Pembelajaran Fisika, 2022)
This study aims to find out: (1) The existence of misconceptions about Straight Motion material in the textbook for Physics class X MIPA-1 SMA Negeri 1 Sambungmacan (2) Profile understanding of the concepts of students in class X MIPA-1 SMA Negeri 1 Sambungmacan. The method used in this study is a qualitative descriptive method. Data and data sources come from textbooks and students of class X MIPA 1 SMA Negeri 1 Sambungmacan. Data was collected by test techniques, questionnaires, and interviews. Techniques to test the validity/validity of data using triangulation techniques of data collection techniques. Meanwhile, the data analysis method uses data simplification, data presentation, and conclusion. The research procedures were preparation, data collection, data analysis/drawing conclusions, and writing reports. The results of this study stated that the student handbook in Class X MIPA-1 SMA Negeri 1 Sambungmacan still contained misconceptions. Misconceptions consist of a lack of completeness of concepts and errors in writing mathematical equations. The criteria for understanding the concept of students in Class X MIPA-1 SMA Negeri 1 Sambungmacan on the Straight Motion materials are divided into Understanding Concepts, Understanding Concepts but Not Sure, Misconceptions, and Don't Know Concepts. Most of the students' misconceptions were in the medium category, as many as 56.67%. Students experience misconceptions about the sub-concepts of Distance and Displacement, Speed, Velocity, and Acceleration, Uniformly Straight Motion and Uniformly Changed Straight Motion, and the Application of Uniformly Changing Straight Motion. The statement of the highest student misconceptions in the sub-concept of the Application of Regular Changing Motion. The causes of misconceptions that exist in students come from student participants, teachers, teaching methods, textbooks, and other causes such as learning facilities.